Market Orientation, Hotel Chain Group And Strategic Management Accounting Usage - Antonius Singgih Setiawan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2020)
The growth effect of the hospitality industry is an increasingly strong competition. Management's focus on the use of strategic management accounting is an important key in anticipating competition. For this reason, this study needs to identify factors that can influence the use of strategic management accounting by hotel management. This study aims to explain the effect of market orientation and hotel chain groups on the use of strategic management accounting in the hospitality industry. A total of 134 questionnaires are distributed to the hotel general managers in Southern Sumatra region. The number of questionnaires used in this study is 118 (88.06%). The data are analyzed using a statistical method of multiple regression. The statistical software used to estimate the model is SPSS software version 21. Research findings indicate that market orientation and hotel chain groups have a positive impact on the use of strategic management accounting in the hotel industry. An important contribution of this research is that the research findings confirm that market orientation is an important factor in the implementation of strategic management accounting, and hotel chain groups are new things that can be identified in strategic management accounting research.